PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) MELALUI KONSELING INDIVIDU TERHADAP KECANDUAN ROKOK PADA SISWA PONDOK PESANTREN DARUL QUR’AN KAMPAR TAHUN AJARAN 2014/2015 - Jumiati Jumiati '; Tri Umari Tri Umari; Zulfan Saam Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Smoking dipsomania in the students’ environment of course really constrains the achievement of education goal. This research purposes are 1) to know the description of smoking addicted level of student before given the SEFT therapies. 2) To know theraphy applying process of SEFT via individual counselling in decreasing smoking addicted level of the students. 3) To know the description of students smoking addicted level after given the SEFT theraphies. This research uses pre-experimental method designed one group pretest posttest design. The sample of this research are 5 students which experience smoking dipsomania. The dipsomnia level of konseli F before given the theraphy is 70%, decreases until 0% after given the therapy and increases back on post test both of as 66,6%. On konseli D, before given the therapy, the addicted level is as big as 80%, decrease until 0% and increases back on post test both of as 63,3 %. On konseli H before given the theraphy is 73,3%, decreases until 0% after given the therapy and increases back to 46,6 %. On konseli R before given the theraphy is 66,6%, increases bbecome 70 % after given the therapy. But, on post test researcher could not find out how the level of smoking dipsomnia of R since R move to SMK. On konseli A, before given the theraphy is 50%, the pretest result is unknowledgeable because he goes home and never back to the boarding school since the first test, but he returns to the Pesantren Darul Qur’an Boarding School on post test and if it was compared with pre- test result,the addicted level of the smoking dipsomnia decrease to 46,6%.Key Words: Smoking Dipsomania, SEFT Therapy, Individual Counselling.